2019
DOI: 10.1111/avsc.12409
|View full text |Cite
|
Sign up to set email alerts
|

Initial understory vegetation responses following different forest management intensities in Illyrian beech forests

Abstract: Background and questions: How forest vegetation responds to disturbance continues to be a focal point, especially in the context of biodiversity conservation. To investigate the short-term effects of forest management on understory vegetation, we asked: (a) Are there any plant indicator species associated with different felling intensities? (b) What are the differences in abundance of plant functional types along the disturbance gradient? (c) How do typical forest species respond to silvicultural treatments? L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 62 publications
2
21
0
Order By: Relevance
“…These results are in line with other studies that demonstrated the potential of plantation forests to maintain the populations of valuable species (Sutton 1999;Brockerhoff et al 2008). They also highlighted that there is an urgent need to improve our understanding about the effects of disturbance and ecosystem characteristics (e.g., duration and intensity of disturbance, resilience and resistance of ecosystem functions, and recovery time) on the local and regional species composition and diversity (O'Brien et al 2018;van de Leemput et al 2018;Kermavnar et al 2019).…”
Section: Discussionsupporting
confidence: 87%
“…These results are in line with other studies that demonstrated the potential of plantation forests to maintain the populations of valuable species (Sutton 1999;Brockerhoff et al 2008). They also highlighted that there is an urgent need to improve our understanding about the effects of disturbance and ecosystem characteristics (e.g., duration and intensity of disturbance, resilience and resistance of ecosystem functions, and recovery time) on the local and regional species composition and diversity (O'Brien et al 2018;van de Leemput et al 2018;Kermavnar et al 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Although partial cutting and canopy gaps promoted the establishment of many light-demanding, non-forest plant species, it is always important to ask how typical forest specialists (including tree species) responded to intensive cutting treatments. In our previous study [36], we have shown that these understory species, presumably more sensitive to disturbance, tolerate a wider range of light conditions and are, shortly after cutting, able to persist in canopy gaps.…”
Section: Discussionmentioning
confidence: 86%
“…Tree cutting was performed between June and August 2012. Detailed information about our experimental design can be found in the works of [36,37].…”
Section: Study Design and Vegetation Sampling Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…In most IM sites, most disturbances occurred in the overstory canopy, resulting in the reduction of tree-layer cover and consequent increases in light reaching the forest floor. As shown in many previous studies [61][62][63], typical forest understory species, presumably more sensitive to disturbance, are able to tolerate a wider range of light conditions.…”
Section: Discussionmentioning
confidence: 60%